Configuration of the Cultural Identity of Islamic Studies Professors in Mataraman through the Lens of Geertz - Moch. Muwaffiqillah; Syamsul Huda; Indana Zulfa; Brett Aaron Huggins (Prodi Sosiologi Agama, 2025)
This study explores the configuration of cultural identity among professors of Islamic studies at state Islamic higher education institutions (PTKI) in the Mataraman region of East Java, Indonesia. Drawing on Clifford Geertz’s santri–priyayi–abangan framework, the research examines how professors negotiate their self-identities within Javanese socio-religious structures. Employing an interpretive ethnographic approach, this study is based on in-depth interviews with professors of Islamic studies from three PTKI—IAIN Kediri, UIN Sayyid Ali Rahmatullah Tulungagung, and IAIN Ponorogo—complemented by participatory observation of academic rituals, religious gatherings, and institutional practices, as well as analysis of relevant institutional documents. The findings reveal a dynamic interplay between academic professionalism and pesantren-based cultural heritage. While most informants identify primarily as professional Islamic intellectuals rather than traditional kyai or priyayi, many embody hybrid cultural affiliations. Their achieved status as state-recognized professors often contrasts with community perceptions rooted in religious authority and pesantren lineage. This identity configuration points to the emergence of a new social formation—the elite santri—characterized by academically sanctioned authority that remains culturally resonant. The study contributes to a nuanced understanding of contemporary Islamic academia and shifting patterns of religious authority in Javanese Muslim society.